A new Leach protocol based on ICH-Leach for adaptive image transferring using DWT - Abdelali Zbakh; Mohamed Taj Bennani (Universitas Ahmad Dahlan, 2019)
Nowadays, the rapid development and the miniaturization of CMOS image sensors in the last years allowed the creation of WMSN (Wireless Multimedia Sensor Network). Therefore, transferring images through the network becomes an important field of research. The main goal is to transmit the data from a sensor node to another to reach finally the Sink node. Thus, routing protocols play an important role in managing and optimizing the node's resources particularly the energy consumption. Therefore, some routing protocols are known by their ability to save energy and extend the lifetime of the network such as Leach protocol and derived variants. However, multimedia content transferring was not a priority for these protocols. In this paper, the main idea is to adapt ICH-Leach [1], for image transferring. This protocol was tested in a previous work and has given good performances against Leach [2], balanced Leach [3] and MLD-Leach [4]. In fact, the Haar wavelet transform is used, in the application layer, to extract the resolution level to be used in image transmission, depending on the rate flow between the sensor node and the sink node. This paper provides statistics concerning the lifetime of the network, the energy consumption and statistics related to receive images using the peak signal-to-noise ratio (PSNR). The Castalia framework is used for simulation, obtained results show the efficiency of the proposed approach by network lifetime extending and more images transmitting with better quality compared to other protocols.